The more technology the better? A comparison of teacher-student interaction in high and low technology use elementary EFL classrooms in China. (August 2019) - Li, Guofang; Sun, Zhuo; Jee, Youngeun
Abstract: While the inclusion of multimedia technology enables diverse learning activities in English as a foreign language (EFL) instruction, its influence on classroom interaction is under-examined. To address this gap, this comparative study examines the impact of technology use on teacher-student interaction patterns (i.e., initiation-response-feedback or IRF patterns) in technology-enhanced primary EFL classrooms in a rural school district in China. Six class videos were selected, three from teachers with high and three with low technology use respectively. Conversation analyses of these class videos revealed that technology use played a negative role in facilitating communicative classroom discourses, with high technology use teachers using more display questions and directives and facilitating less spontaneous or authentic output from students in the target language. In addition, teachers in both types of classroom provided little but almost identical amounts of corrective feedback, suggesting a minimal impact of technology on teacher feedback patterns. The findings reveal extensive teacher-centered technology use in EFL classrooms and warrant an urgent need to discuss the importance of and potential approaches to enhancing EFL teachers' pedagogical awareness and competence in technology-assisted language instruction.